Prevalence, risk and protective factors of burnout among Korean hospitalists - Kyung Mee Park; Jaewoong Kim; Taeyoung Kyong; Hee Youn Han; Song Yi Song; Se Yoon Park (PLoS ONE, 2025)
Background Burnout among healthcare professionals is a critical factor which affects patient safety, treatment outcomes, and the quality of care. This is especially important for hospitalists who manage inpatient care, yet no studies have been conducted on this issue in Korea. This study aimed to investigate burnout and psychiatric symptoms among hospitalists in Korea, as well as to identify the risk and protective factors associated with these issues. Materials and methods A cross-sectional online survey was conducted targeting all hospitalists in Korea (n=303), and 24.1% (n=79) completed the survey. The Maslach Burnout Inventory–Human Services Survey was used to measure burnout; the Depression, Anxiety, and Stress Scales was used to assess psychiatric symptoms; and the Insomnia Severity Index was used to evaluate sleep disturbances. Risk and protective factors against burnout were assessed using a 5-point Likert scale. Results More than half of the respondents reported high graded burnout for two domains: depersonalization (50.6%) and reduced personal accomplishment (57%). Conflicts with caregivers, excessive workload, and long working hours were common risk factors for both burnout domains. The satisfaction with nonclinical work was identified as protective factor in depersonalization, and the availability of a research mentor and cap on daily inpatient load per hospitalist were protective factors in reduced personal accomplishment. In the correlation analysis, the maximum number of inpatients and hospitalists per hospital was a significant factor in reducing burnout. Conclusions This study revealed a high graded burnout rate of more than 50% in depersonalization and reduced personal accomplishments domain among Korean hospitalists, and found the risk and protective factors against burnout. The development of targeted interventions to mitigate burnout based on this study could enhance the mental well-being of healthcare professionals and improve the overall quality of medical care.